Translating evidence-based knowledge objects into practice - Scheuer, John Damm (Frontiers in Health Services, 2023)
This paper aims to show how organizational translation theories and models may supplement implementation science with a new process perspective on how knowledge objects such as Cochrane reviews, clinical guidelines and reference programs are implemented in practice in healthcare organizations. They build on Bruno Latour’s idea about translation that states that the spread in time and space of anything – including knowledge objects - is in the hands of people and that each of these people may act in many different ways, letting the token drop, modifying it, deflecting it, betraying it, adding to it, or appropriating it (Latour, 1986). Implementation science theories, models and frameworks often try to identify general aspects of processes and variables that influence implementation processes. In contrast, translation theories and models build on a process view that uses the sequence of events, activities and choices by translators situated in time as well as in space to explain how outcomes of translation/implementation processes came about. The paper develops some implementation relevant propositions about translation of knowledge objects in healthcare organizations that may inform further research. Moreover, it discusses how organizational translation studies and implementation science may supplement each other.